UTILIZATION OF ETHANOLAMINE AS CARBON DIOXIDE ABSORBER FOR - Asdiana Irma Yusuf; Muhammad Zakir; Maming Maming (Hasanuddin University, 2015)
Utilization of ethanolamine as carbon dioxide absober for estimating of coral age from langkai island via LSC (Liquid Scintillation Counting) method has been done. Focus is to analyze coral reefs taken from Langkai island surface which is relatively far from the influence of human activities. Chemical preparation was carried out by using a mixture of NaOH with H2O2 30% followed by a mixture of HClO4 with H2O2 30%, and finally with HCl solution to produce a clean sample with 8.6% weight reduction. Carbonate matrix samples as CO2 is produced by reaction with HCl 10% and absorbed by ethanolamine solution 30% as carbamate complex. The total carbon in the sample solution is 4.542 grams obtained through decreased method after and before absorbtion process. Total carbon in 8 mL sample is 0.2477 grams. Radiocarbon dating method based on the measurement of the specific activity of the samples acquired from the result of LSC (Liquid Scintilation Counter)Hidex 300 SL counting. Age of coral reefs was counted from specific activities data and average activities of modern carbon by using radioisotope decay rate formula. The spesific activities of 14C in coral reefs from Langkai island is 14.55 ± 1.1 dpm/gC. Finally the age of coral reefs was estimated 415.01 ± 91.08 years.Keywords: Coral reefs, LSC (Liquid Scintilation Counting), radiocarbon dating, Spermonde islands.